Green Synthesis of Copper Nanoparticles Using Leaf Extract of Ocimum sanctum and its Antimicrobial Activity - Zambare, Pradnya; Survase, Avinash; Kanase, Shivangi (International Journal of Pharmaceutical Investigation)
Objectives: We reported a non-toxic, low-cost and environmentally friendly green synthesis technique for the manufacture of copper nanoparticles (Cu NPs) utilizing Ocimum sanctum (O. sanctum) leaf extract to prevent hospital-acquired and Methicillin-resistant pathogenic bacterial infections strains. Materials and Methods: The biogenic synthesis of Cu NPs via chemical precipitation method using O. sanctum phytochemical extract as stabilizing and reducing agent. Cu NPs syntheses are characterized using UV-visible spectroscopy (UV-vis spectroscopy), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) to analyze and confirm size and nature of Cu NPs. Results: UV-vis spectroscopy of Cu NPs showed an absorption peak at 528 nm with calculated band gap 2.1 eV. XRD analysis indicates crystallite nature of Cu NPs having an average size 48 nm. FTIR showed involvement of O. sanctum extract biomolecules in capping process Cu NPs. The hexagonal morphology structure of Cu NPs nanoparticles is observed by SEM analysis. Cu NPs showed antibacterial activity against Staphylococcus aureus (38.66 ± 1.15 mm), Escherichia coli (43.33 ± 1.15 mm), Pseudomonas aeruginosa (21.66 ± 0.57 mm) and Proteus vulgaris (42.66± 0.57 mm). Conclusion: We report synthesis of simple, inexpensive and eco-friendly O. sanctum mediated Cu NPs. The biophysical characterization techniques used for analyze size, shape and nature of nanoparticles. The 32 ug/ml Cu NPs concentration showed excellent antimicrobial activity against Gram positive and Gram-negative bacteria. Cu NPs efficiently used to prevent Proteus vulgaris mediated infection.
Keywords: Antimicrobial activity; Green nanotechnology; Ocimum sanctum; Cu NPs; XRD; SEM.